Non-intercostal access for video-assisted thoracic surgery— analysis of technical advantages and disadvantages - Zieliński, Marcin; Gwozdz, Pawel; Wilkojc, Michal; Kosinski, Sylweriusz; Fryzlewicz, Edward; Nabialek, Tomasz; Pankowski, Juliusz; Kwiatkowski, Robert (Journal of Thoracic Disease; Vol 10, Supplement 32 (November 20, 2018): Journal of Thoracic Disease (Enhanced Recovery: The Evidence Supporting Best Perioperative Care in Thoracic Surgery), 2018)
Background: Video-assisted thoracoscopic surgery (VATS) lobectomy has become an accepted method for the treatment of early-stage non-small-cell lung cancer (NSCLC). The standard VATS approach is an intercostal one which is often followed by postoperative pain due to injury of the intercostal nerve. The non-intercostal techniques of VATS include the subxiphoid, transcervical, transdiaphragmatic and transoral procedures. Methods: The technical difficulty of operative management of the anatomical structures during VATS anatomical resection are compared for the intercostal, subxiphoid and transcervical approaches. Results: Some operative steps have different range of difficulty, which are analyzed in detail. Conclusions: The clearest advantages of the non-intercostal approaches include less postoperative pain and superradial bilateral mediastinal lymphadenectomy in case of the transcervical approach. However, the non-intercostal approaches are more technically demanding procedures, which therapeutic role has to be clarified in the future.